Upregulation of long noncoding RNA zinc finger antisense 1 enhances epithelial–mesenchymal transition in vitro and predicts poor prognosis in glioma - Qiao-Li Lv; Shu-Hui Chen; Xue Zhang; Bao Sun; Lei Hu; Qiang Qu; Yuan-Tao Huang; Gui-Hua Wang; Yan-Ling Liu; Ying-Ying Zhang; Hong-Hao Zhou (Tumor Biology)
Increasing evidence indicates that long noncoding RNAs play important roles in development and progression of various cancers. Zinc finger antisense 1 is a novel long noncoding RNA whose clinical significance, biological function, and underlying mechanism are still undetermined in glioma. In this study, we reported that zinc finger antisense 1 expression was markedly upregulated in glioma and tightly correlated with clinical stage. Moreover, patients with high zinc finger antisense 1 expression had shorter survival. Multivariate Cox regression analysis provided a clue that, probably, zinc finger antisense 1 level could serve as an independent prognostic factor for glioma. Functionally, zinc finger antisense 1 acted as an oncogene in glioma because its knockdown could promote apoptosis and significantly inhibit cell proliferation, migration, and invasion. Furthermore, zinc finger antisense 1 silencing could result in cell cycle arrest at the G0/G1 phase and correspondingly decrease the percentage of S phase cells in both U87 and U251 cell lines. Moreover, it was found that silenced zinc finger antisense 1 could impair migration and invasion by inhibiting the epithelial–mesenchymal transition through reducing the expression of MMP2, MMP9, N-cadherin, Integrin β1, ZEB1, Twist, and Snail as well as increasing E-cadherin level in glioma. Taken together, our data identified that zinc finger antisense 1 might act as a valuable prognostic biomarker and potential therapeutic target for glioma.